Brecht sourcebook - Martin, Carol J.; Bial, Henry, 1970- (Worlds of performance., 2000)
Bertolt Brecht is one of the most prolific and influential writer-directors of the twentieth century. This fascinating anthology brings together in one volume many of the most important articles written about Brecht between 1957 and 1997. The collection explores a wide range of viewpoints about Brecht's theatre theories and practice, as well as including three plays not otherwise available in English: The Beggar or The Dead Dog, Baden Lehrstuck and The Seven Deadly Sins of the Lower Middle Class. Editors Martin and Bial have brought together a unique compendium which cove.